The house that science built - Pollard, Michael (New York, New York Facts On File Publications, 1987)
This book explains the technology of modern life - the many types of housing, how buildings are constructed, and materials used in the home such as metal, wood, china and plastics.
Includes index
Keywords: Dwellings -- Juvenile literature; Dwellings -- Electric equipment -- Juvenile literature